Loss of Protein Kinase Csnk2b/CK2β at Neuromuscular Junctions Affects Morphology and Dynamics of Aggregated Nicotinic Acetylcholine Receptors, Neuromuscular Transmission, and Synaptic Gene Expression - Nane Eiber; Michael Rehman; Bojana Kravic; Rüdiger Rudolf; Marco Sandri; Said Hashemolhosseini (Cells, 2019)
The protein kinase Csnk2/CK2 is important for cell proliferation, differentiation, and survival. Previously, we showed that CK2 binds distinctive proteins at neuromuscular junctions (NMJs) of mice and phosphorylates some of them. CK2 likely stabilizes clustered nicotinic acetylcholine receptors (AChRs). In the absence of the β-subunit of CK2 in skeletal muscle fibers, mice develop an age-dependent decrease of grip strength accompanied by NMJ fragmentation and impairments of neuromuscular transmission. However, the precise role of CK2β regarding the clustering of AChRs and downstream signaling at NMJs is unknown. Here, we compared conditional CK2β-deficient mice with controls and found in the mutants (1) a lower decrement of endplate potentials after repetitive stimulation and decrements of nerve-evoked compound muscle action potentials decayed more rapidly after synaptic transmission was partially blocked, (2) that their muscle weakness was partially rescued by administration of an acetylcholine esterase inhibitor, (3) fragmented NMJs and impaired AChR clustering was detected in muscles and cultured muscle cells, (4) enlarged myonuclei, (5) impaired synaptic gene expression, and (6) a high turnover rate of their AChR clusters in vivo. Altogether, our data demonstrate a role for CK2 at the NMJ by maintaining a high density of AChRs and ensuring physiological synaptic gene expression.